Host Lipid Mediators in Leprosy: The Hypothesized Contributions to Pathogenesis - Silva, Carlos A. M.; Belisle, John T. (Frontiers in Immunology, 2018)
The spectrum of clinical forms observed in leprosy and its pathogenesis are dictated by the host’s immune response against Mycobacterium leprae, the etiological agent of leprosy. Previous results, based on metabolomics studies, demonstrated a strong relationship between clinical manifestations of leprosy and alterations in the metabolism of ω3 and ω6 polyunsaturated fatty acids (PUFAs), and the diverse set of lipid mediators derived from PUFAs. PUFA-derived lipid mediators provide multiple functions during acute inflammation, and some lipid mediators are able to induce both pro- and anti-inflammatory responses as determined by the cell surface receptors being expressed, as well as the cell type expressing the receptors. However, little is known about how these compounds influence cellular immune activities during chronic granulomatous infectious diseases, like leprosy. Current evidence suggests that specialized pro-resolving lipid mediators (SPMs) are involved in the down-modulation of the innate and adaptive immune response against M. leprae, and that alteration in the homeostasis of pro-inflammatory lipid mediators versus SPMs are associated with dramatic shifts in the pathogenesis of leprosy. In this review, we discuss the possible consequences and present new hypotheses for the involvement of ω3 and ω6 PUFA metabolism in the pathogenesis of leprosy. A specific emphasis is placed on developing models of lipid mediator interactions with the innate and adaptive immune responses and the influence of these interactions on the outcome of leprosy.